Inflammation and Immune Response of Intra-Articular Serotype 2 Adeno-Associated Virus or Adenovirus Vectors in a Large Animal Model. (11th January 2012) - Ishihara, Akikazu; Bartlett, Jeffrey S.; Bertone, Alicia L.
Abstract : Intra-articular gene therapy has potential for the treatment of osteoarthritis and rheumatoid arthritis. To quantify in vitro relative gene transduction, equine chondrocytes and synovial cells were treated with adenovirus vectors (Ad), serotype 2 adeno-associated virus vectors (rAAV2), or self-complementary (sc) AAV2 vectors carrying green fluorescent protein (GFP). Using 6 horses, bilateral metacarpophalangeal joints were injected with Ad, rAAV2, or scAAV2 vectors carrying GFP genes to assess the in vivo joint inflammation and neutralizing antibody (NAb) titer in serum and joint fluid. In vitro, the greater transduction efficiency and sustained gene expression were achieved by scAAV2 compared to rAAV2 in equine chondrocytes and synovial cells. In vivo, AAV2 demonstrated less joint inflammation than Ad, but similar NAb titer. The scAAV2 vectors can induce superior gene transduction than rAAV2 in articular cells, and both rAAV2 and scAAV2 vectors were showed to be safer for intra-articular use than Ad vectors.